2012
DOI: 10.1073/pnas.1206330109
|View full text |Cite
|
Sign up to set email alerts
|

Persistent and reversible consequences of combat stress on the mesofrontal circuit and cognition

Abstract: Prolonged stress can have long-lasting effects on cognition. Animal models suggest that deficits in executive functioning could result from alterations within the mesofrontal circuit. We investigated this hypothesis in soldiers before and after deployment to Afghanistan and a control group using functional and diffusion tensor imaging. Combat stress reduced midbrain activity and integrity, which was associated to compromised sustained attention. Longterm follow-up showed that the functional and structural chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 52 publications
2
47
0
Order By: Relevance
“…These inconsistencies in cingulum FA are likely due to differences in study design (eg, cross-sectional, no control group), or inclusion of non-deployed controls. These differences, along with the observation that deployment has been shown to reduce white matter microstructure integrity in the brainstem (Van Wingen et al, 2012), suggest that future studies aimed at understanding the neurobiology of PTSD in combat-deployed PTSD patients must include a combatexposed control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These inconsistencies in cingulum FA are likely due to differences in study design (eg, cross-sectional, no control group), or inclusion of non-deployed controls. These differences, along with the observation that deployment has been shown to reduce white matter microstructure integrity in the brainstem (Van Wingen et al, 2012), suggest that future studies aimed at understanding the neurobiology of PTSD in combat-deployed PTSD patients must include a combatexposed control group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, whole-brain analyses were performed to provide a comprehensive unrestricted survey of potential treatment-related white matter differences. We included a deployed, trauma-exposed comparison group to control for the effects of time and deployment (Van Wingen et al, 2012). Using treatment outcome as an indicator, patients with remitted PTSD were compared with patients who still had a PTSD diagnosis after treatment (persistent PTSD), and with combat controls.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that survival training and battlefield stress impairs working memory, reaction time, and visual-spatial capacity which can lead to operational or battlefield errors [1] [7]. Combat stress has also been shown to affect midbrain activity and attention, including reduced functional connectivity between the prefrontal cortex and midbrain, which persisted at an 18 month follow-up [3]. Surging military rates of PTSD [8] and suicide in the wake of the US military operations in the Middle East [9], illustrate the need for training to prepare individuals to recognize and cope with severe stress both during performance and in the aftermath.…”
Section: Introductionmentioning
confidence: 97%
“…While exposure to moderate, acute stress is associated with improved performance, long-term severe stress can reduce fine motor performance [1], attention [2], and cognitive function [3] due to biological and neural mechanisms. Unmitigated stress is associated with a number of disease states including cardiovascular disease, depression, and cancer [4], and with a significant reduction in productivity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mounting evidence suggests that many differences in brain structure may actually represent risk factors for the development of PTSD rather than consequences of the disorder (Gilbertson et al, 2002;Pitman et al, 2006). However, two groups conducting studies before and following deployment or combat exposure demonstrated changes in brain structure, function, and functional connectivity following war zone deployment (Admon et al, 2009(Admon et al, , 2013avan Wingen et al, 2011van Wingen et al, , 2012, although not directly due to the development of PTSD. Exploratory analyses to evaluate the robustness of our results demonstrate the level of heterogeneity present in the data.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%